Stk24 protects against obesity-associated metabolic disorders by disrupting the NLRP3 inflammasome - Qin, Qiang; Shou, Jia’nan; Li, Mengjie; Gu, Meidi; Meng, Zhuoxian; Xu, Pinglong; Meng, Hua; Wang, Xiaojian (Cell reports (Cambridge), 2021)
Adipose tissue macrophages (ATMs) regulate the occurrence of obesity and its related diseases. Here, we found that serine/threonine protein kinase 24 (Stk24) expression is downregulated significantly in ATMs in obese subjects or obese subjects with type 2 diabetes and mice fed a high-fat diet (HFD). We further identified that glucolipotoxicity downregulated Stk24 expression in ATMs. Stk24-deficient mice develop severe HFD-induced metabolic disorders and insulin insensitivity. Mechanistically, Stk24 intervenes in NLRP3 inflammasome assembly in ATMs by associating directly with NLRP3, decreasing interleukin-1β (IL-1β) secretion. Accordingly, Stk24 deficiency in the hematopoietic system promotes NLRP3 inflammasome activation, which contributes to exacerbation of metabolic disorders. Intriguingly, Stk24 expression correlates negatively with body mass index (BMI) and the levels of glucose, cholesterol, triglycerides, and low-density lipoprotein in human subjects. These findings provide insights into the function and clinical implications of Stk24 in obesity-mediated metabolic disorders. [Display omitted] •Glucolipotoxicity downregulates Stk24 expression in ATMs•Stk24 in ATMs negatively regulates high-fat-diet-induced metabolic disorders•Stk24 inhibits metabolic disorders by interfering with NLRP3 inflammasome activation•Stk24 binds to NLRP3 and suppresses inflammasome assembly and activation Qin et al. find that Stk24 works as an inhibitor of obesity-associated metabolic disorders by suppressing NLRP3 inflammasome activation. Reduced expression of Stk24 is associated with obesity and metabolic disorders in mice and humans. The findings provide insights into the function and clinical implications of Stk24 in obesity-mediated metabolic disorders.